Gangrenous cystitis in a 42-year-old male - De Rosa, Antonella (BMJ Publishing Group, 2011)
Gangrenous cystitis is now an extremely rare condition since the widespread use of antibiotics. The authors report a case of gangrenous cystitis in a previously fit and normal 42-year-old male who presented in acute urinary retention. He underwent a partial cystectomy during an exploratory laparotomy for clinical deterioration and peritonitis. Diagnosis of this rare disease is challenged by its low incidence and lack of characteristic pathognomic features, resulting in delayed diagnosis and increased morbidity and mortality. The authors review the literature to date on the aetiology, presentation, diagnosis and management of gangrenous cystitis and emphasise the importance of early and aggressive surgical management.